Body is an experiment of the mind: with and without self - Spindler, Stephanie, author; Voss, Gary Wayne, advisor; Hendry, Kenneth, committee member; Sullivan, Patrice M., committee member; Williams, Ronald G., committee member (Colorado State University. Libraries, 2002)
Materials and process are aspects in developing the work from my own experience including empathizing with the human condition. The work itself is not conceptual but inspired by conceptual structures that influence form, giving a sense of experience separate from a narrative; an experience for the body, prompting memory. The work is about a psychological space, an illusion or suggestion of emotion, or thought, about being and not being, and the tension that exists in that space.
Keywords: Mixed media (Art); Psychology and art